Magnitude of Psychological Distress Among Medical and Non-Medical Students During the Late Phase of the COVID-19 Pandemic in West Bengal: A Cross-Sectional Study - Udisa Das; Arunima Ganguly; Dibakar Haldar; Asish Mukhopadhyay (University Library System, University of Pittsburgh, 2024)
Background: COVID-19 pandemic led to drastic changes worldwide significantly affecting mental health of students. This study aimed to assess psychological distress due to COVID-19 in students during the late phase of pandemic and to establish correlation of academic course, socio-demographics and knowledge-attitude-practices (KAP) with depression and anxiety. Methods: A cross-sectional study was conducted in Kolkata, from March to April 2022 among undergraduate medical students and undergraduate students from engineering and general science colleges, via purposive and snowball sampling. Survey questionnaire was circulated via Google forms through social media. It included Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, Fear of COVID-19 scale 2020, KAP regarding COVID-19 and socio-demographics. Data were analyzed using SPSS(Version 22.0) by estimating mean, standard deviation, median, interquartile range and displayed by charts and tables. Mann-Whitney U test/non-parametric ANOVA and Chi-square tests were used for drawing statistical inferences. P-value of <0.05 was considered significant. Results: Total 421 responses were included: 219 medical and 202 non-medical students. Most participants were male (58.67%). Prevalence of depression was 58.42% among non-medical students and 81.73% among medical students.  Prevalence of anxiety was 50.99% among non-medical students and 76.25% among medical students. Medical students had significantly better scores for knowledge and attitude (p=0.001 in both). Anxiety was influenced by residence (p=0.018), mode of travel (p=0.012), and having relatives or friends affected by COVID-19 (p=0.03). Conclusion: High prevalence of depression and anxiety among college students, especially medical students, highlights the need for student wellness activities and better mental health services in colleges across India.